Fault-tolerant tracking control for a non-linear twin-rotor system under ellipsoidal bounding - Kukurowski, Norbert; Mrugalski, Marcin; Pazera, Marcin; Witczak, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
A novel fault-tolerant tracking control scheme based on an adaptive robust observer for non-linear systems is proposed. Additionally, it is presumed that the non-linear system may be faulty, i.e., affected by actuator and sensor faults along with the disturbances, simultaneously. Accordingly, the stability of the robust observer as well as the fault-tolerant tracking controller is achieved by using the H[infinity sign] approach. Furthermore, unknown actuator and sensor faults and states are bounded by the uncertainty intervals for estimation quality assessment as well as reliable fault diagnosis.
Keywords: fault-tolerant control; simultaneous faults; external disturbances; non-linear system; robust fault estimation; fault detection and diagnosis